2013
DOI: 10.1378/chest.12-1899
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Burden of COPD-Related Visits in the ED

Abstract: Background:Little is known about the population-based burden of ED care for COPD. Methods: We analyzed statewide ED surveillance system data to quantify the frequency of COPDrelated ED visits, hospital admissions, and comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 21 publications
4
13
0
Order By: Relevance
“…In the present study, we found that adults at highest risk of frequent ED visits were more likely to have public insurance, and to have lower socioeconomic status. These results support prior reports of higher rates of frequent ED visits for COPD among these vulnerable populations [10,11]. Although the precise role of lower socioeconomic status to this disparity in COPD healthcare utilizations is unclear [5], the asthma literature would suggest that differences in health beliefs, less self-management education, and limited access to preventive and specialist care in this population might lead to a heavier reliance on episodic symptom treatment and emergency care [32].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we found that adults at highest risk of frequent ED visits were more likely to have public insurance, and to have lower socioeconomic status. These results support prior reports of higher rates of frequent ED visits for COPD among these vulnerable populations [10,11]. Although the precise role of lower socioeconomic status to this disparity in COPD healthcare utilizations is unclear [5], the asthma literature would suggest that differences in health beliefs, less self-management education, and limited access to preventive and specialist care in this population might lead to a heavier reliance on episodic symptom treatment and emergency care [32].…”
Section: Discussionsupporting
confidence: 91%
“…The primary limitation of this study, shared by other studies based on data from large national surveys, is its reliance on the self-reporting of the physician diagnoses of chronic bronchitis, emphysema, asthma, and the ten comorbid conditions. However, it is encouraging that the results of this study corroborate some of the results from previous studies based on both self-reported data 28 and studies of state-based 23 and national 22 registries of utilization. A second limitation of our study is its lamentable lack of diagnoses for mental health disorders, as prior studies have shown that depression and substance abuse in patients with COPD contribute tangibly to health care utilization.…”
Section: Discussionsupporting
confidence: 87%
“…A second limitation of our study is its lamentable lack of diagnoses for mental health disorders, as prior studies have shown that depression and substance abuse in patients with COPD contribute tangibly to health care utilization. 23 , 29 Last, because our study is observational in nature, we make no claims of causality.…”
Section: Discussionmentioning
confidence: 99%
“…1 The WHO estimated that 65 million people have moderate-severe COPD, accounting for 5% of all causes of death in 2005. 2 …”
Section: Introductionmentioning
confidence: 99%